Semipolar GaN‐based heterostructures on foreign substrates (Phys. Status Solidi B 1/2016). Issue 1 (January 2016) - Scholz, Ferdinand; Caliebe, Marian; Gahramanova, Gulnaz; Heinz, Dominik; Klein, Martin; Leute, Robert A. R.; Meisch, Tobias; Wang, Junjun; Hocker, Matthias; Thonke, Klaus
Abstract : Semipolar GaN heterostructures are promising for future green light emitters, because respective GaInN quantum wells are characterized by a reduced piezo‐electric field as compared to their polar counterparts, which is expected to be advantageous for the radiative recombination probability of the carriers in LEDs and laser diodes. However, such structure, requiring an epitaxial growth direction in other than the conventional polar c‐direction, are typically blamed by huge defect densities, particularly if grown on foreign substrates like sapphire. Several papers in this Special Issue (e.g. Scholz et al., Meisch et al., Leung et al., Hashimoto et al., de Mierry et al.) concentrate on a method where the eventually semipolar growth initially proceeds in c‐direction by etching trenches into the sapphire wafer which have a c‐plane side facet. Hence lower defect densities can be realized. The cover figure shows schematically such structure including an in‐situ deposited SiN nanomask layer for further defect reduction (red) and semipolar quantum wells on top (green). Such semipolar LEDs emit quite intense light (bottom pictures) in the green spectral range. See more details in Scholz et al. (pp.13–22 ) and Meisch et al. (pp.164–168 ) in this issue.